2008
DOI: 10.1287/orsc.1070.0301
|View full text |Cite
|
Sign up to set email alerts
|

Product Demography of De Novo and De Alio Firms in the Optical Disk Drive Industry, 1983–1999

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
126
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 51 publications
2
126
0
1
Order By: Relevance
“…Recent research that is more specific to the topic of firms' responses to technological change has suggested that institutional forces might affect different organizations differently. For instance, Sine, Haveman and Tolbert (2005) suggest there are differential institutional implications for firms that invest in new technologies versus existing technologies, while Khessina and Carroll (2008) show that de novo firms might be forced to conform more to institutional expectations than de alio firms. In contrast, our work addresses the systematic divergence in pressures from institutions for de alio firms from different industries that are following similar product-market strategies using the same technology.…”
Section: Contributionsmentioning
confidence: 99%
“…Recent research that is more specific to the topic of firms' responses to technological change has suggested that institutional forces might affect different organizations differently. For instance, Sine, Haveman and Tolbert (2005) suggest there are differential institutional implications for firms that invest in new technologies versus existing technologies, while Khessina and Carroll (2008) show that de novo firms might be forced to conform more to institutional expectations than de alio firms. In contrast, our work addresses the systematic divergence in pressures from institutions for de alio firms from different industries that are following similar product-market strategies using the same technology.…”
Section: Contributionsmentioning
confidence: 99%
“…Indeed, high product entry rates associate empirically with high demand (Connor, 1981) and with large market size (Ingram & Roberts, 1999). Likewise, low product disappearance rates correspond with high demand (de Figueiredo & Kyle, 2006), low demand uncertainty (Astebro & Michela, 2005;Hitsch, 2006), high initial revenues (Chisholm & Norman, 2006), and high sales and shipments in complementary and symbiotic industries (Cottrell & Nault, 2004;de Figueiredo & Kyle, 2006;Khessina & Carroll, 2008).…”
Section: Products As Market Rationalitymentioning
confidence: 99%
“…Nonetheless, Khessina and Carroll (2008) found that after controlling for product entry, products entering later in an industry display higher exit rates (Khessina & Carroll, 2008); another study found an inverted U-shape relationship between the order of product entry and product exit (Requena-Silvente & Walker, 2009). …”
Section: Products As Market Rationalitymentioning
confidence: 99%
See 2 more Smart Citations